2018
DOI: 10.1002/hpm.2648
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hospital readmissions in internal medicine patients: Application of Andersen's Model

Abstract: Although some predictors of readmission were unalterable, they could be used to identify high-risk patients. Innovative approaches targeting discharge planning and postdischarge care for patients with high comorbidity scores and long length of stay could reduce internal medicine patients' unplanned readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
3
12
1
Order By: Relevance
“…We also found that longer LOS within the index admission puts patients at risk of multiple and longer readmission events. This result is partially consistent with some other studies on internal medicine patients conducted in civilian settings (4,17,20), which examined a much shorter post-discharge period than the present study. Still, a longer LOS seems to be an important factor for predicting the risk of repeated future readmissions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also found that longer LOS within the index admission puts patients at risk of multiple and longer readmission events. This result is partially consistent with some other studies on internal medicine patients conducted in civilian settings (4,17,20), which examined a much shorter post-discharge period than the present study. Still, a longer LOS seems to be an important factor for predicting the risk of repeated future readmissions.…”
Section: Discussionsupporting
confidence: 93%
“…This approach also enabled the identification of high-risk patients who are the most appropriate target group for reducing the overall number of readmission events. To date, numerous studies have examined 30-day readmission for various severe diseases and suggested that it is associated with the male sex (OR=1.83, P=0.02), ICU stay (OR=2.5, P=0.049), LOS (4), comorbidity score (17), and different socioeconomic factors (18), although similar studies are rare in military settings.…”
Section: Discussionmentioning
confidence: 99%
“…Within the scope of other studies, between 50.6% and 61.7% of women used health care (Dhingra et al, 2010;Hong et al, 2019;Conner, 2012;Jin et al, 2019;Roh et al, 2017;Liu et al, 2019). However, some studies determine that men (around 53%) receive more health services (Holtzman et al, 2015;Kaya et al, 2019).…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…In this study, it was revealed that the most married people (72.7%) used a family medicine. If we look at similar studies on the subject, it was determined that 52.9% to 84% of the married people use health service (Heider et al, 2014;Hong et al, 2019;Jin et al, 2019;Ogunsanya et al, 2016;Kaya et al, 2019;Franck et al, 2020;Liu et al, 2019). Some studies determine that those who receive health services (66% and 84.6%) are not married (single, divorced and widows) Hirshfield et al, 2018;Lee et al, 2020).…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…3,6 Previous studies have identified factors associated with hospital admissions in older populations. [7][8][9] However, there is a paucity of research that reports predictors of urgency-specific (planned and unplanned) hospital admission.…”
Section: Introductionmentioning
confidence: 99%